Sistema brasileiro de precedentes judiciais à luz do dever de fundamentação das decisões judiciais e os direitos fundamentais de acesso à justiça e da razoável duração do processo - Debortoli, Karina (2024)
The fundamental rights of access to justice, both in a broad and strict sense, and the right to a reasonable duration of proceedings are priorities for legal practitioners, especially given the high volume of cases pending in Brazil. Data from the National Council of Justice (CNJ) indicate that in 2023, there were 83.8 million cases in progress, with an estimated timeframe of two years and five months required to clear the existing backlog, disregarding the influx of new cases. In this context, this thesis examines the impact of binding precedents, from the perspective of the duty to provide reasoned judicial decisions, on the realization of these fundamental rights. Adopting the deductive method, the thesis conducts a critical and flexible interpretation of the Brazilian justice system, emphasizing how precedents can contribute to the speed and predictability of judicial decisions. The duty to provide reasoning, established in Article 93, IX, of the Federal Constitution, is presented as an essential element for ensuring the legitimacy of judicial decisions and adherence to the standards outlined in Article 489, §1, of the Code of Civil Procedure. When properly observed, binding precedents promote a swifter justice system without undermining the fundamental right of access to justice. The thesis underscores that, within the paradigm of the Democratic Rule of Law, binding precedents play a central role in guiding judges and courts in resolving similar cases, contributing to the predictability and stability of judicial decisions. It argues that, in fulfilling the duty to provide reasoning, judges must consider applicable precedents, justifying any distinctions or the adoption of procedural techniques that shorten the duration of proceedings without compromising the rights of the parties. The thesis also emphasizes the necessity of cultivating a precedent culture in Brazil, which includes the training and preparation of legal practitioners, as well as the enhancement of technological systems to ensure the proper identification and application of precedents. Furthermore, it highlights the responsibility of judges in taking ownership of their decisions, aiming to build a solid and effective system of precedents. Data from the CNJ illustrate the effectiveness of precedents, with 6,236 cases resulting in the suspension of 2,770,663 actions, representing a ratio of 1 to 444. These figures demonstrate the potential of precedents to reduce the accumulation of cases, ensuring broad access to justice and reasonable case durations. The unification and improvement of judicial technological tools are identified as essential measures to strengthen the application of precedents and consolidate their efficacy. The thesis concludes that binding precedents are indispensable instruments for addressing the challenges faced by the Brazilian justice system, contributing to the realization of fundamental rights and promoting a swifter, more predictable, and legitimate justice system, in alignment with the values of the Democratic Rule of Law